3D printing and nanosensors - Behera, A. (Elsevier, 2021)
In this decade additive manufacturing is playing a vital role in fabrication of various types of industrial equipment. 3D printing is a computer-aided design process offering various advantages that increase the market size for nanosensor smart manufacturing. Nanotechnology provides an advanced platform to improve the sensing properties of sensors, due to the larger surface area than that of microsensors. This chapter describes the fundamentals of 3D printing as well as nanotechnology applications for nanosensors. Various 3D printed nanosensors including physical sensors, biosensors, and chemical sensors are discussed. By incorporating 3D printing, many more complex shapes of nanosensors can be easily formed. Research is ongoing to improve the attributes of nanosensor fabrication as well as decrease the cost of the 3D printed nanosensors. Â© 2021 Elsevier Inc. All rights reserved.